Analysis and comprehensive assessment of the development and application of the neural network dialogue system ChatGPT - D. A. Machueva; D. R. Baraev; T. M.-A. Bechurkaev (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. Today, significant and in many ways sensational results are being achieved in the field of artificial intelligence systems, and the ChatGPT bot, which is based on the GPT-3 neural network, is called a real revolution in the world of technology.The aim of the study is to analyze and evaluate the application features, advantages and limitations, as well as development factors and reasons for the extraordinary popularity of the neural network dialogue system ChatGPT.Method. A review of domestic and foreign sources, systematization of data, analysis of the architecture and mechanism of action of the neural network was carried out. Result. Functions, opportunities, scopes and risks of using ChatGPT are summarized and evaluated.Conclusions. The main function of ChatGPT – text generation based on given input data – allows to effectively solve a wide range of tasks that have not been automated before, and the quality of the solution is comparable to human work. However, it is important to avoid the risks associated with the possibility of abuse and receiving incorrect and malicious responses from artificial intelligence. This requires control measures, the development and introduction of standards and norms.